Micelles Based on Lysine, Histidine, or Arginine: Designing Structures for Enhanced Drug Delivery - Xie, Li; Liu, Rong; Chen, Xin; He, Mei; Zhang, Yi; Chen, Shuyi (Frontiers in Bioengineering and Biotechnology, 2021)
Natural amino acids and their derivatives are excellent building blocks of polymers for various biomedical applications owing to the non-toxicity, biocompatibility, and ease of multifunctionalization. In the present review, we summarized the common approaches to designing and constructing functional polymeric micelles based on basic amino acids including lysine, histidine, and arginine and highlighted their applications as drug carriers for cancer therapy. Different polypeptide architectures including linear polypeptides and dendrimers were developed for efficient drug loading and delivery. Besides, polylysine- and polyhistidine-based micelles could enable pH-responsive drug release, and polyarginine can realize enhanced membrane penetration and gas therapy by generating metabolites of nitric oxide (NO). It is worth mentioning that according to the structural or functional characteristics of basic amino acids and their derivatives, key points for designing functional micelles with excellent drug delivery efficiency are importantly elaborated in order to pave the way for exploring micelles based on basic amino acids.